The quality of MDF workpieces machined in CNC milling machine in cutting speeds, feedrate, and depth of cut - De Deus, Priscila Roel [UNESP]; Alves, Manoel Cleber de Sampaio [UNESP]; Vieira, Fabio Henrique Antunes [UNESP] (Springer Nature, 2015)
Medium density fiberboard (MDF) is an industrial product created from lignocellulosic fibers and resin through the combined action of pressure and heat. Have homogeneity, dimensional stability and mechanical strength similar to solid wood. Milling is a machining method widely used within furniture industries; and despite the noteworthy relevance of the subject, there are few specific works dealing with the MDF milling process using computerized numerical control machines. It is increasingly necessary a programmed machining able to generate suitable surface to coatings, allowing for minimum waste and maximum efficiency, besides the decrease of the tool wear. The irregular surface after machining reduces the quality of the final product; this characteristic is defined by measuring the roughness of MDF panel workpieces. Thus, it is possible to quantify the surface quality and improve the machining process with cutting speed, feed rate, depth cut among others. It was observed that roughness exhibited lower values in higher cutting speeds and low feed rates. The 1 mm depth of cut showed optimized surface results. It was concluded that the parameters studied here significantly influence the finishing, resulting in irregular surfaces that can reduce the quality of products.
Keywords: Panels; Roughening; Wood